Single‐Cell Immune Profiling Suggests Non‐Classical Monocyte Is Associated Immunodepression in Tuberculosis Treatment Non‐Responders - Yiqun Xiong; Yahong Qu; Ying Wang; Dongliang Zhang; Hao Shen; Weixin Wang; Junshun Gao; ZhenBo Wang; Zhihong Shen; Yang Che (Journal of Cellular and Molecular Medicine, 2026)
ABSTRACT Sputum culture conversion (SCC) at 2 months is an early indicator of tuberculosis (TB) treatment response, yet the associated immune alterations remain incompletely defined. We performed single‐cell RNA sequencing on peripheral blood mononuclear cells from eight TB patients, stratified by 2‐month SCC status. Non‐responders showed a relative enrichment of non‐classical monocytes and higher TB progression risk scores. CellChat analysis inferred altered IL16 and TRAIL communication involving these cells. CD4+ Tregs in non‐responders showed higher LGALS9 expression and inferred GALECTIN signalling towards cytotoxic lymphocyte subsets; cell‐level LGALS9 co‐expression correlated with HAVCR2 and TIGIT in non‐responders. Mature NK subclusters showed distinct enrichment profiles. These results describe an observational, transcriptomic and computationally inferred immune network associated with early treatment non‐response. They generate candidate biomarkers and hypotheses for prospective protein‐level and functional validation.